Matrix Discriminant Analysis Evidenced Surface-Lithium as an Important Factor to Increase the Hydrolytic Saccharification of Sugarcane Bagasse - Almeida Scarcella, Ana Silvia de; Somera, Alexandre Favarin; Carreira Nunes, Christiane da Costa [UNESP]; Gomes, Eleni [UNESP]; Vici, Ana Claudia; Buckeridge, Marcos Silveira; Moraes Polizeli, Maria de Lourdes Teixeira de (Mdpi, 2019)
Statistical evidence pointing to the very soft change in the ionic composition on the surface of the sugar cane bagasse is crucial to improve yields of sugars by hydrolytic saccharification. Removal of Li+ by pretreatments exposing -OH sites was the most important factor related to the increase of saccharification yields using enzyme cocktails. Steam Explosion and Microwave:H2SO4 pretreatments produced unrelated structural changes, but similar ionic distribution patterns. Both increased the saccharification yield 1.74-fold. NaOH produced structural changes related to Steam Explosion, but released surface-bounded Li+ obtaining 2.04-fold more reducing sugars than the control. In turn, the higher amounts in relative concentration and periodic structures of Li+ on the surface observed in the control or after the pretreatment with Ethanol:DMSO:Ammonium Oxalate, blocked -OH and O- available for ionic sputtering. These changes correlated to 1.90-fold decrease in saccharification yields. Li+ was an activator in solution, but its presence and distribution pattern on the substrate was prejudicial to the saccharification. Apparently, it acts as a phase-dependent modulator of enzyme activity. Therefore, no correlations were found between structural changes and the efficiency of the enzymatic cocktail used. However, there were correlations between the Li+ distribution patterns and the enzymatic activities that should to be shown.
Keywords: lithium; sugarcane bagasse; saccharification; glycosyl-hydrolase; ToF-SIMS; surface ion distribution; second-generation ethanol; pretreatment